A new spider family record for Hispaniolaa new species of Plectreurys (Araneae: Plectreuridae) in Miocene Dominican amber - Penney, David (Zootaxa, 2009)
The Plectreuridae is a relatively small, ecribellate, haplogyne spider family consisting of only two extant genera. Kibramoa Chamberlin has seven described species restricted to the USA and Mexico (Gertsch 1958) and Plectreurys Simon is known from 22 species, with similar distributions (Gertsch 1958, Jiménez 2006), but also including Cuba and Costa Rica (Alayón 1993, 2003). In addition, a single fossil species Palaeoplectreurys baltica Wunderlich, known only from the holotype, has been described from the Eocene Baltic amber of Europe (Wunderlich 2004). Additional fossils are known from the Jurassic of China and these are currently being described by Selden (pers. comm. 2009), who also questions the placement of Palaeoplectreurys Wunderlich in this family. Thus, the extant forms may represent relicts of a family more widespread in the past. Little is known about the biology of this family, although they are unusual among ecribellate haplogynes in possessing eight, rather than six eyes. They are nocturnal, hunting spiders, which live in a silken tube that they seldom leave, rather like the closely related Segestriidae (Gertsch 1958). However, males leave their tube upon maturity to go in search of females, at which point they become more susceptible to entrapment in tree resin seeps (Penney 2002). The tibia of leg 1 in males of Plectreurys has a distinctive stout retrolateral process towards the distal end, which bears a strong spine. These coupling spurs, which are absent in Kibramoa and Palaeoplectreurys are presumed to be used for restraining or positioning the female during mating.